Strategic Indeterminacy and Online Privacy Policies: (Un)informed Consent and the General Data Protection Regulation - Green, Daniel (International journal for the semiotics of law = Revue internationale de sémiotique juridique, 2025)
Article 12 of the General Data Protection Regulation (GDPR) requires data controllers to provide data subjects with any information relating to data processing operations “in a concise, transparent, intelligible and easily accessible form, using clear and plain language.” Linguistic inclusivity of privacy policies is no longer a matter of style, but has been a binding legal requirement under the new data protection framework. Article 5 GDPR sets forth the requirements of lawfulness, fairness and transparency and prohibits any data processing operations which do not meet the standards of specification, explicitness and legitimacy of processing purposes [ 29 ]. In this study, a quantitative and qualitative analysis of linguistic indeterminacy in a corpus of 350 online privacy policies is presented and it is argued that a considerable number of data controllers continue to make use of strategic vagueness in the context of purpose limitation, therefore potentially prejudicing compliance with the GDPR. A legal-linguistic perspective on the current challenges of informed consent in European data protection law is provided. Finally, it is concluded that while the GDPR has contributed significantly to the linguistic empowerment of the data subject, the framework fails to satisfy the expectation of creating a participatory culture (see [ 36 ]) with a high degree of informational self-determination.